Fiscal Policy Challenges for Countries that Join the EU - Blaceri, Ilda Kadrimi; Ribaj, Artur (European Journal of Economics and Business Studies, 2019)
The choice of fiscal policy is one of the most controversial issues of the role of government in a country’s social and economic life, not only by economists, but by a wider range of people.This article will discuss some of the issues on which the fiscal policy debate remains open. The analysis will focus on both the theoretical approach and the role that fiscal policy has played in our country, going further on some suggestions for the future. It will also analyze the status of fiscal policy in Albania seen in the context of fiscal sustainability. It will address the role that fiscal policy plays in social issues and the role of politics in the choice of fiscal policy. In a country with high level of poverty and an economy that requires large investments, the choice of fiscal policies is a controversial issue. This issue will focus on their impact on the economy of our country. The article concludes with conclusions and recommendations.